Seasonal and interannual changes in planktonic biomass and community structure in eastern Antarctica using signature lipids - Skerratt, J; Nichols, PD; McMeekin, TA; Burton, HR (Marine Chemistry, 1995)
The total lipid, fatty acid, sterol and pigment composition of water column particulates collected near the Australian Antarctic Base, Davis Station, were analysed over five summer seasons (1988-93) using capillary GC, GC-MS, TLC-FID and HPLC. Maximum lipid concentrations usually occurred in samples collected in December and January and corresponded with increased algal biomass. Polar lipids were the dominant lipid class. Both lipid profiles and microscopic observations showed significant variation in biomass and community structure in the water column both intra- and interannually. During the period of diatom blooms (predominantly Nitzschia spp.) the dominant sterol and fatty acid were trans-22-dehydrocholesterol and 20:53, respectively, which were accompanied by a high 16:17c to 16:0 ratio. Very high polyunsaturated fatty acid and total lipid concentrations were measured during diatom blooms in the area. Bacterial markers increased in concentration after the summer algal blooms in each year. C30 sterols also increased in concentration during the latter half of all summers. Samples collected from the fjords contained greater biomass and diversity in algal and bacterial markers than samples from coastal sites. Signature lipids for the prymnesiophyte Phaeocystis sp., thought to be seasonally abundant in Antarctic waters, were identified in field samples over the five summer seasons studied. Blooms of this alga exhibited high 14:0, brassicasterol, low levels of polyunsaturated fatty acids and a low 16:17c to 16:0 ratio. Based on the lipid profiles, the overall abundance of Phaeocystis sp. throughout the five summer seasons was sporadic and in most summers the abundance was low; these findings suggest Phaeocystis sp. is not always a major alga in this coastal region of Antarctica. 1995 Elsevier Science B.V. All rights reserved.